This action might not be possible to undo. Are you sure you want to continue?
Structure
2.1
3.2
SUBGROUPS
Introduction
Objcct~ves
Subgroups Properties of Subgroups Cyclic Groups Summary
3.3
3.4
3.5
3.1 INTRODUCTION
You have studied the algebraic structures of integers, rational numbers, real numbers and, finally, complex numbers. You have noticed that, not only is Z c Q c R c C, but the operations of addition and multiplication coincide in these sets. In this unit you will study more examples of subsets of groups which are groups in their own right. Such structures are rightfully named subgroups. In Sec. 3.3 we will discuss some of their properties also. In Sec. 3.4 we will see some cases in which we obtain a group from a few elements of the group. In particular, we will study cases of groups that can be built up by a single element of the group. Do study this unit carefully because it consists of basic concepts which will be used again and again in the rest of the course.
Objectives
After reading this unit, you should be able to
e
e e
define subgroups and check if a subset of a given group is a subgroup or not; check if the intersection, union and product of two subgroups is a subgroup; describe t h structure and properties of cyclic groups.
3.2
SUBGROUPS
You may have already noted that the groups (Z,+), (Q,+) and (R,+) are contained in the bigger group (C,+)of complex numbers, not just as subsets but as groups. Ail these are examples of subgroups, as you will see.
Dffinition : Let (G,*) be a group. A nonempty subset H of G is called a subgroup of G if
i)
11)
a * b E H ff a, b E H, i.e.,
* is a binary operation on H,
(H,*) is itself a group.
!<o.by definition, (Z,+) is a subgroup of (Q,+),(R,+) and (C,+).
'J,~w, if (H, *) is a subgroup of (G,*), can the identity element in (H,*) be different from the r:fckneityelement in (G,o) ? L e t us see. If h is the identity of (H,*), then, for any a E H, I1 * a a * 11 = a. However, a E H c G. Thus,a * e = e * a = a, where e is the identity in G. r'herefore, h * a = e * a.

3 1 1 right cancellation in (G,*), we get h = e.
Thus, whenever (H, *) is a subgroup of (G,*),e
E
H.
Hence. Then H is a subgroup of G iff a. b E H = $ a. provided that there is no confusion about the bhary operations. . does a I E H for every a E H? E 1 and the discussion before it allows us to make the following remark. (G.*). Proof : Firstly. But then. Therefore. Remark 1: (H. aE H * aI E H. Finally.. + is also abelian. .*) is a subgroup of (G. for any S. by Remark 1. Therefore. be f ] Gm Since. Then. S I c*. then a.Now you may like to try the following exercise. if a.+) is an abelian group. Show that 2. since 1 E S. b E H * ab' E H. a (b')I = ab E H. *) if and only if t i) ii) iii) ~ E H . bI E H. We would also like to make an important remark about notation here. a + b = b + a V a. let us assume that H I G . ] is the inverse of [. eaI = a' E H. aaI = e E H. Example 2: Consider G = MzX3( C ) . H is a subgroup.*). zl z21 E S. we shall just say that H is a subgroup of G . for any a E H.3a E H. . is the additive identity and You can see that Iis a binary operation on G . H is closed under the binary operation of the group. since H + @. Also. Remark 2 : If (H. Show that Solution : We define addition on G By . Check that (G. Example 1 : Consider the group (c*. a b c P q r [ d e f ] +[s t =[ a + p b + q c + r d + s e + t f + u I . 0 = [ 1. b H ~ * a * b ~ H. a. *) is a subgroup of (G. by Theorem 1. While going through these you may realise the fact that a subgroup of an ahelinn group is abelian. Again. Therefore. Conversely. We will also denote this fact by H 2 G . Theorem 1 : Let H be a nonempty subset of a group G. Now we discuss an important necessary and sufficient condition for a subset to be a subgroup. b E H. Subgroups E 1) If (H. b E C. a . is. E H Let us look at some examples of subgroups now. by Remark 1. the set of all 2 x 3 matrices over C. bI 3 abI E H. Thus.). z2 E Solution : S * @ .*) is a subgroup of (G.+) is an abelial~ group.
0 S r < s. Example 4 : Any nontrivial subgroup of (Z. for E H #@ and % . Now. (R)= (A GL3(R) det(A) = I ) is a I subgroup of (Gb(R). then st = (s) + (s) + . SL3(R) .).ns.. det (AB') = det (A) det(B') = det (A) . Itrn. That is.e. Therefore. since (k) E H and (k) > 0... Before going to the next example. r = m .. 42m. B E SL3(R). If k < 0. Thus. Now sZ H Why 7 Well. Also.e 0 0 c.). i E H). ns e H. since det (A) = 1and det (B) =I.. we see tha 0 a. E 2) Show that for any group G. since 0 E S. S G N. we must have r = 0. let us see what the nth roots of unity are. ( ( e ) is called the trivial su'rgrcnp.. Therefore. +) is of the form mZ. mrms = m(rs) Therefore...] S. mZ # I$. Now. Hence. A E GL3(R) iff det (A) t 0. for some m e N. rns E mZ. GL3 (R). Try the following exercise now. Thus. That is. then st = s + s + . r E Z. S [O 0 0 a c b]. Thus.. Note that m is the least positive integer in mZ. i. that is. for mr. st E H . [: .d b.) The next example is very important.. consider any element st E sZ. then H = mZ. Show that S1. Clearly.= S I G . S S. Now. E s. If t > 0. Then we will show that if H is a subgroi~p of Z. and you may use it quite often. If k > 0. Example 3 : Consider the set of all invertible 3 x 3 matrices over R. + s (t times) E H. r n = ns. by the wellordering principle (Sec. If t < 0. If t = 0. det @) : . 0 E mZ. where m m Z = { mt 1 t E Z) = { 0. let m E H. SL3(R) I GL3(R)... then st = 0 E H. say s. I . s is the least positive integer that belongs to H.then k (k) E S.1. But H is a subgroup of Z and m.Elementary Croup ~ h e b r ~ Now.2). Thus..b e H t f a . @t E Z. there is a nonzero integer k in H. . r E H. rn = ns + r for some n. I i > 0. By minimality of s in S. :$ $. Now. Also. So we have proved that H = sZ.. 1. Therefore. E Since H # {0). E N and Solution : We will first show that mZ is a subgroup of Z. for which complex numbers z is zn= 1.+ (s) (t times) E H. k3rn . That is. H # {O). then +4. Solution : The 3x3 identity matrix is in SL3(R). AB' E SL3(R) : .1)S has a least element.. let H t (0) be a subgroup of Z and S = { i E mZ. H E sZ. . for A. (el arid G are subgroups of G.f ] . mZ is a subgroup of Z.6. sZ H.6. b ~H.. By the division algorithm (see Sec.t I$.
if n = 6. 0 . Thus.. Does this mean that as k ranges over Z and 8 ranges over 7 we get distinct nth 2nk roots of l ? Let us find out. . the circle of radius one with centre (0. ? COST 2nm + i sin 2 T if and 2nk 2nm only if ...O)).* From the appendix to Unit 2.4.. 2. w2. that is. then zn = 1. 2nk k E Z. = (1. by De Moivre's theorem. i. is an argument of zl and e2 that of z2. .. Now.ww'). w2.. we see that 0 + 2nk (k E Z) and n0 are arguments of the same complex number.. z = 2m 2nr cos 7 + i sin n . + i sin y.3...an'.e..1 + w +a2+ a 3+ . They form the vertices of a regular hexagon. Thus.... .. cos 7 +.. where i . cos (0) + i sin (0) = rn (cos ne + i sin no). Moreover. If z = r (cose + i sine) is an nth root of 1. no can take any one of the values 2nk. 0 I r c n ... 2n then show that If n > 1 and w = cos .. This will happen iff k = m+nt. where r = 1 z I and 8 is an argument of z....e. Subgroups 2zk i sin . Fig. In Fig. we get an nth root of unity.. 5.. and zg... zg. Equating the modulus of both the sides of (1). Using this we will try to find the nth roots of 1. (1) " 1.. if 0 . . c j d = cos % + i sin 2l n for 0 5 j 5 n1 (using Dc Moivre's theorem). 1.= 2nt for some t E Z.e. 22. . Now.. where n E N. r =l..since o is the Greek letter omcga.+ on' = 0. ... 1 = zn = rn (COS ne + i sin ne).. we get r On comparing the arguments of both sides of (I).. and these are all the nth roots of unity.. For example. 1: 6th roots of unity 2n 2n Then all the nth roots of 1 are 1. n n k = m (mod n).. corresponding to every 7 in Z. then el + e2 is an argument of zl z2. 1 you can see that all these lie on the unit circle (i. w. you know that the polar form of a nonzero complex number z E C is z = r ( C O S +~i sine). we get the 6th roots of 1 as'%. Let U. E 3) 2n.rl 2 zj= cos 6 + i sin 6 j = 0. Thus... zl. The following exercise shows you an interesting property of the elements of U. i. let o = cos 7 + i sin tt..
So. . * 3 . Now. E U . Thus. b E Z(G) and for any x E G.& Then K is a subgroup of G.e. Z(G) is the set of those elements of G that commute with every element of G.. \ Theorem 3 : Let G be a group. The proof is very simple. For example. premultiplying by a'. \ Let us look at subgroups of Z. is a subgroup' of c*. Before ending this section we will introduce you to a subgroup that you will use off and on.'oni oi for all 1 Ii < n. Then.e properties of subgroups. if mi E U. H be asubgroup of G and K be a subgroup of. ab E Z(G).i.tf x E G.Let mZ and kZ bk two subgroups of 2. Thus.). K f $ and abI E K +f a. a xa I = aI x. (c'. K < G.. Show that rnZ is a subgroup of kZ iff k 1 r n . we can write i+j = qn + r for q. suppose L rn. Theorem 2 : The centre of any group G is a subgroup of G. The following exercise will give you some practice in obtaining the centre of a group. for every natural number n we have a finite subgroup of order n of c*. if G is abelian. : .  0. d = oi+j multiplication. I . is closed under then wi . # c*. X E Thus. since w n = 1. = wn= 1. . Hence. is the set z ( G ) = { ~ EG I X ~ = ~ X ~GI. Z(G) is subgroup of G. . for any a. 3 PROPERTIES OF SUBGROUPS Let us start . b e K. Also. Proof: Since e E Z(G). a € Z(G) +ax = x a W x c G. Note that U. Therefore. ( 'a b ) g '= a(bx) = a(xb) = (ax)b = (xa)b = x (ab). postmultiplying by aI. Definition : The centre of a group G. on' is the inverse of Finally. S~lutlon : We need to show thatpZ E M o k rn. But = oqn+r = (O")Q. 0 I r 5 nI. with showing that the relation 'is a subgroup of' is transitive. mr= 0' E U . Now mZ I I s kZ =+ m e rnZ s kZ Conversely. let mi. E 4) Show that Z(S3) = [I). (Hint : Write the operation table for S3. Example 6: In E x q p l e 4 we have seen that my subgroup of Z is of the form mZ &r some m E N.) Let us now discuss som. in the context of Theorem 3. ol We will now show that Z(G) I G. Z(G) f 0. U .. denoted by Z(G).Elementary Croup Theory NOWwe are in a position to obtain a finite subgroup of Example 5 : Show that UnI Solution : Clearly. U . is a finite group of order n and is a'subgroup of a n infinite group. r E Z. 3 aI E Z(G). then 0 5 ni 5 n1 and oi. c*. =+ x = aI xa V x E G. then Z(G) = G. by the division algorithm. U. Proof : Since K S H. Now.
B. n K 4.in mtr rubgmup of. Note that proving this amounts to proving that AUBIGdAcBorBgA. The next exercise says that this is the only situation in which AUB is a subgroup of G.Hence. = {I. Yow. m = kr for some r E 2.denotes. Which subgroups of 2 is 9Z a subgroup o f ? E Z such that n = mt.. S is not a subgroup of (Z. (1 2) 1 and K = {I. b E H. (1 3 211. we have the following result. (1 3). Theorem 4 : If H and K are two subgroups of a group G. Proof : Since e E H and e E K. but 1 = 32 is neither in 2 2 nor in 3 2 . 2 E 2 2 S. two subgroups 2 2 and 3 2 of 2.)    Let us now see what we mean by the product of two subsets of a group G. I € nI Hi is also a E 6) ab & AUB.abI E K.where e is the identity of G.By Theorem 1 . b E K. Now. (2Z ) (32 ) = { (2m) (3m) ( m. (1 2). do you think the union of two (or more) subgroups is again a subgroup? Gonsider the. t). In this example we find that the product of two subgroups is a subgroup. AUB $ G.n E 2 ) = 62. But is that always so? Consider the group s. Now. Let S = 2 2 U 32. Thus. n E Z ) = { 6mn( m.Then. The whole argument of Theorem 4 remains valid if we take a family of subgroups instead of just two subgroups.is a family of subgroups of a group G.Take a E A \ B and b E B \A. (Remember. (Hint : Suppose A B and B A. (1 3)). Hence. Let A and B be two subgroups of a group G. mZ c kZ. 3 E 3 2 G S. if A E. abI E H. b E H fl K. The product of A and B is the set AB = { ab ( a E A. Hence. since a. Hence. Hence. AUB need not be a subgroup of G. Subgroups I E5) We will now discuss the behaviour of subgroups under the operations of intersection and union. b E B). e E H n K. subgroup of G . H n K is a subgroup of G. Thus. then AUB = B is a subgroup of G. and let t Then n = mt = (kr) t = k(rt) E kZ . Theorem 4' : If {Hilie.L. you may like to try the next exercise. then H fl K is also a subgroup of G. (1 2 31. let a. Now. Prove that AUB is a subgroup of G iff AsBorBcA. (1 2) is the permutation ( :: )and (1 2 3) is the permutation . For example. mZ I kZ iff k I m. (2 3). then . Definition : Let G be a group and A. But. since a. and its subgroups H = (1. if A and B are subgroups of G. Now. Then show that . abI E H I7 K. Similarly. B be nonempty subsets of G. it is enough to show that ab' E H fl K. Now consider any n E mZ. S. T~US H. Thus.
Thus. HK c KH. Theorem 5 : Let H and K be subgroups of a group G. Conversely. But then hk = (kI h')I =k '. kh E HK. I . then K EF.')h.) So. Then. Therefore. E K. k . If <S> = G. Definition : If S is a subset of a group G. F = { H 1 HSGandSsH}. Then a = hk and b = hl kl for some h. k' h' = h. Proof : Firstly. I . E K. let a. Since e = e 2 E HK. 3 h2k2E HK such tho( (kk'. then the smallest subgroup of G containing S is called the subgroup generated by the set S. k. Hence. then we say that G is generated by the set S. (Because if K is a subgroup of G HEB containing S. assume that HK 5 G. (kk. Therefore.' = h2kz. since it is not even closed under composition. and that S is a set of generators of G . HK 5 G. We claim t h a t F z I$. KH cHK. b E HK. Therefore.' E KH. (1 21. Then (kh)I = h' k' E HK. Then HK is a subg~. H c K. Try the following exercise now. ((kh)')I E HK.') h. E 7) Is AB a subgroup of S4. and is written as <S>. But HK I G.) = (hh2)k2E HK. Then abI = (hk) (k. that is. ( 1 2 ) 0 (I 3)} = { I. Now. we have shown that HK = KH.oup of G if and only if HK = KH. (1 3 211 HK is not a subgroup of G. by Theorem 4'. ab' = h(h2k.Elementary Group Theory NowHK = { I . h. (1 31.')= h [ (kk. T~us. Let hk E HK. (1 2)}? The next topic that we will take up is generating sets.<s>= ~ I I HG. of G .' h.SGH}.']. HK # $. We liave to prove that HK IG. (Note that (1 3) o (1 2) = (1 2 3) HK. Let G be any group and S a subset of G. assume that HK = KH. Now.4 CYCLIC GROUPS In this section we will briefly discuss generating sets. and then talk about cyclic groups in detail. Why? Doesn't G E ! F ? Now. Thus.') h. since HK I G. We will show that HK = KH. when will the product of two subgroups be a subgroup? The following result answers this question. Now. The following result is a nice corollary to Theorem 5. that is. Consider the family 7 of all subgroups OF G that contain S. then HK is a subgroup of G. by Theorem 1. Thus. kl for some hi E H. (1 4)) and B = {I. where A = { I. . we will show that KH c HK. A  3. Corollary : If H and K are subgroups of an abelian group G. then <S> = {e). Then (hk)' = k' h' E HK. I o ( l 3 ) . Therefore. ( 1 2 ) . If S = $. Let kh E KH. Note that HEJ nl H is a subgroup ii) H is the smallest subgroup of G containing S.' E KH = HK.) HEF n n These observations lead us to the following definition. hl E H and k.
Z is generated by the set of odd integers S = { +I. Note that. (1 2)3 = (1 2). . the definition of <S>. + ) is a group generated by S. Then. . a? a? ... And hence.. us see why. This definition is much easier to work with than the previous one. by A. Since al. Show that a subset S of N generates the group Z of all integers iff there exist sl. E S a n d n . q . by Theorem 1.. Before giving examples. .. A subgroup H of a group G is called a cyclic subgroup if it is a cyclic group.. m E <S>.k. This shows that <S> = A. Theorem 6 : If S is a nonempty subset of a group G. . For example. ... . Thus.. wherea. k nk E E 2). let us see why <S> c A. Then < (1 2) > = { I.. +n. E 10 shows that a group can have many generating sets. b f n l ) ~ A.... a!' E <s> E < S >..... Try the following exercises now. . we will give an alternative way of describing <S>. since (1 2)2= I.. . k .. if ( G. it will follow that <S> Since any a E S can be written as a = a l ...b y r .. Thus. < (1 2) > is a cyclic subgroup of S3 and 2 2 = <2> is a cyclic subgroup of Z: We would like to make the following remarks here. S G A.. And hence. ..nk in Z such that nlsl .. f 3 . For example. bq ) ' a"k) (Grrnr . and so on. then I a i E s f o r 1 < i < k . <S> = Z. Therefore.. (1 2)).then < a > . ~ Z.. W e In E Z)...n k 21. . Thus. f i . ~ Proof :Let A = { a l n l2 : a ..... ) Let . s G <s>and <s> is a subgroup 04 G. a> (($ a?. then <T> = G. by y = blfnlb2m2....... G K.. then any element of G is of the form nl al + n 2 a 2 + . i. Since S # $. E 8 gives an example of a group that is generated by only one element.'p'i = 1. (Hint : Apply Theorem 6. Show that S = (1) generates Z. A is a subgroup of G.. We give such a group a special name.. k. . n.. ... ii) All the elements of < a > = ( an n E Z) may or may not be distinct.. a. bj E S for 1 5 i 2 k.... n 1 . ak E Now ........ + nksk =I.e. A c <S>.. we say thal G is finitely generated.a. ..a .. a I ai S for 1 2 i 5 k.. Then x = alnl a> Then x p l = (aY1 = ( a : . This is because c a > is the smallest subgroup of G containing a.. Thus... Then m = 2's where r 2 0 and s E S... . a. Definition : A group G is called a cyclic group if G = < {a) > for some a usually write < {a) > as < a >. Now let x..nk <s>= {ayla? .. . take I a = ( 1 2) E S3. 1 < j 5 r.. a.. Let m E Z... Note that < a > = { a n E G. n2. . n ..If the set S is finite..sk in S and n. . A is a subgroup of G containing S.) E 8) E 9) + E 10) Show that if S generates a group G and S cT E G.. y E A. . A # $. Remark 3 : i) If K 5 G and a E K. <S> E A. We will show that A is a subgroup containing S.
ab] and the binary operation on K4given by the table. then H = < e >. b) and < ab > = { e. xy = y X for all x. ab). a. <xk > G H. Now let us look at another nice property of cyclic groups. Elementary Group Theory I Now you can try the following simple exercises. If H = {e). 0 I r Ik1. E 11) Show that if G # {el. Therefore. it would have to be generated by e. Theorem 7 : Every cyclic group is abelian.following exercise. Thus.) S has a least element. < b > = { e. That is. .1. Then 3 n E Z such that x% H. We will now prove a nice property of cyclic groups. a' = a. E 13) Show that S3 is not cyclic.' Theorem 8 : Any subgroup of a cyclic group is cyclic. Also. Use Theorem 7 to solve the. Therefore. n # 0. Then. xy = arn. If it were cyclic. n E Z such that x = am. H is cyclic. But this does not mean that every abelian group is cyclic. < e > = {e) . y = an.1925) The table shows that (K4 . Proof : Let G = < a > = { an I n E Z). We will show that H = < x k > . there exists a positive integer m (i. But k is the ( I * 56 . But. Now. < a > = { e. since xn. a ). Conversely. xk E H. 1. r I Fig! 2: Felix Klein (1849. (xn)I = x" E H. and hence. Thus. a. n or n) such that xm E H. for any x. Since H is a subgroup. y in G. This group is called the Klein 4group. then G # < e >. Thus.. Example 7 :' Consider the set K4 = {e. By the division algorithm n = mk + r where m. b or ab.) is a group. G is abelian. and so on. ( x ~ ) E~ H. Now. K4 is not cyclic. Therefore. By the wellordering principle (see Sec. am = yx.1. a" = a.6.a " am+"= = a n . K4can't be generated by e. Proof : Let G = < x > be a cyclic group and H be a subgroup. the set S = { t E N I xt E H) is not empty. E 12) Show that < a > = < aI > for any a E G.e. Note that Theorem 7 says that every cyclic group is abelian. there exist m. say k. then. 'suppose H # {e). a. a2 = e. y in G. Show that K4is abelian but not cyclic. r E Z. Similarly. let x"be an arbitrary element in H. But then xr = xn* = xn. b. Solution : From the table we can see that K4 is abelian. b or ab. after the pioneering German group theorist Felix Klein. since xk E H. Consider the following example.
Thus. all these are cyclic. i. H < xk >. a. And then.e. Let us now see what we have done ill this unit. That is. we can have groups whose proper subgroups are all cyclic.least positive integer such that xk E H. E 14) E 15) Show that any nonabelian group must have a proper subgroup other than {e). 5) The definition of a generating set. : .. + con'). b E G.a) (1 + o + o 2 I... Hence. As you can see. Corollary : Let H # {el be a subgroup of < a >. Obtain all the subgroups of Z4. G. k an'= 0. 1) The definition and examples of subgroups. of all permutations on 3 symbols. Its proper subgroups are Subgroups H is a proper subgroup of G if! 1 1 $ G.without the group being cyclic.. 4) The product of two subgroups H and K is a subgroup if md only if HK = KH. But. G $ $. Consider the group S3. but the converse need not be true. 3. : . xI E G. E 3) Since on = 1. . G IG . 6) A cyclic group is abelian. Therefore. by E 13 you know that S3 itself is not cyclic. Try the following exercises now. Using Theorem 8 we can immediately prove what we did in Example 4. 4) From E 14 of Unit 2 recall the elements of S3.. 1 + o + a2+ 0 . :. ... On writing the operation table for S3 YOU will find that only I commutes with every permutation in S3. where n is the least positive integer such that a n E H. 2) The intersectibn of subgroups is a subgroup.  .. xr can be in H only if r = 0. n = mk and xl' = (xVm E < xk >. E I) E 2) Yes. (I. Theoren] 8 says that every subgroup of a cyclic group is cyclic. bI E G. that is. because H is a group in its own right. {el 5. H = < xk >. But the converse is not true. 7) Any subgroup of a cyclic group is cyclic. .. Also for any x E G . {el # $.. abI E G.5 SUMMARY In this unit we have covered the following points.= Since o # 1.. Also eeI = e E {el . 3) The union of two subgroups H and K is a subgroup if and only if H k K or K E H. by Theorem 1. Now we state a corollary to Theorem 8. which you know is  <i>. in which we write down the important point made in the proof of Theorem 8. H is cyclic.. We give such an example now. . Then H = < an >. Now. for a. : . ( 1 4 " ) = 0. but the converse need not be true.
3 a E G. < a > = < aI>. Then 1 E < S >. Conversely. Firstly. : But a E AUB and b E AUB. Since Z4 is cyclic. Now. sk E S and n... (1 4). . since G is nonabelian..sk k.. + nnksk E < S >. Conversely.sk E S and n. . AUB $ G.. 3 sl. : . AB = { I. < 3 > and ( 0 ) . (1 3) Theorem 7.. then ab = c. . 3 2 and itself only. any element of <a> is a " (al) ".UB. 9Z is a subgroup of Z. si E T Y i = I. n = n... a # e. suppose Z = < S >. 3 b E B such that b E A.."' . G # < e >. Since G # {e}.... a r€ < e >...... a contradiction. its subgroups are Z4... .. suppose 3 s. Therefore. . (1 2).... all its subgroups are cyclic.. We know that if A B or B A. AB 5 S4. ab E A..+ nksk = 1. k. : .. Then b = aI c E A. ab 6! P. Since A $ B.for n n Z... nk E Z such that g = s... G # < a >. Therefore.. Then G + {el. .g.. s.. For any n E Z. Since S G T. But. E n Z. : . for any n E Z. < a' > c < a >.'. we see that G = < T >.. (1 2) 2 (1 2) (1 3)). 'l'hen < a > 5 G.. Now.. .. : .... = < S >. nk 6 Z such that nls. if ab E A. by Let G be a nonabelian group. (1 2 4) ). + nksk = 1. < a > E: < aI >. .. S3can't be cyclic.. 3 a E A such that a E B. Since a # e. n = n. 3 and 9. Thus.. Since B 8 A.sl + . 0 : .nk E Z such that n. . then AUB is A or B. : by Theorem 6 . .'.... and hence. Similarly. z We know that G = < S >.. :... : .. a # er for any r : . . for some c E A.sk E S and n. < a > $ G :.. . ab 6! B.. + nzsz + . < 5 >. Since S3is not abelian (e. we will assume that A $ B and B $ A. 3 sl. (1 2) (1 4) = (1 4 2) E AB... Thus. So. w e will show that < a > E < aI > and < a' > E < a >. + . and conclude that AUB $ G. is a subgroup of G. a% 4 aI >. Then.Elementary Group Theory E 5) The divisors of 9 are 1. 3 4 # e in'G. Z = < (1) >.1 = nn.1 E <{I} >. Similarly. for any g E G. ..
This action might not be possible to undo. Are you sure you want to continue?
We've moved you to where you read on your other device.
Get the full title to continue reading from where you left off, or restart the preview.